2004
DOI: 10.1152/ajpheart.00170.2003
|View full text |Cite
|
Sign up to set email alerts
|

Augmented systolic response to the calcium sensitizer EMD-57033 in a transgenic model with troponin I truncation

Abstract: . Augmented systolic response to the calcium sensitizer EMD-57033 in a transgenic model with troponin I truncation. Am J Physiol Heart Circ Physiol 286: H1785-H1792, 2004. First published December 23, 2003 10.1152/ ajpheart.00170.2003.-Myocardial stunning is a form of acute reversible cardiac dysfunction that occurs after brief periods of ischemia and reperfusion. In several animal models, stunning is associated with proteolytic truncation of troponin I (TnI). Mice expressing the same proteolytic TnI fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Furthermore, studies with open chest pig hearts stressed by a stunning protocol, also demonstrated an improvement of contractility with improved mechanical efficiency [79]. A related study has shown that EMD 57033 is potently effective in acutely restoring systolic function in a mouse model harboring a proteolytic truncation of cTnI, cTnI , associated with myocardial stunning [80]. Taken together, these studies indicate that the potential undesirable effects of EMD 57033, such as diastolic abnormalities and impaired relaxation, may not be a problem after all.…”
Section: Emd 57033mentioning
confidence: 96%
“…Furthermore, studies with open chest pig hearts stressed by a stunning protocol, also demonstrated an improvement of contractility with improved mechanical efficiency [79]. A related study has shown that EMD 57033 is potently effective in acutely restoring systolic function in a mouse model harboring a proteolytic truncation of cTnI, cTnI , associated with myocardial stunning [80]. Taken together, these studies indicate that the potential undesirable effects of EMD 57033, such as diastolic abnormalities and impaired relaxation, may not be a problem after all.…”
Section: Emd 57033mentioning
confidence: 96%
“…Second, a quantitation of shifts of these relations to acute interventions may be misleading when based solely on slope, particularly if the data are nonlinear. As depicted in prior studies (28,40) and in Fig. 4, differences between nonlinear ESPVRs can easily be assessed by an area defined between them.…”
Section: Assessment Of Ventricular Functionmentioning
confidence: 98%
“…Changes of this nature are observed if the cross-bridge force generation is itself altered, as has been observed with changes in redox state, with proteolytic cleavage of TnI in postischemic stunned myocardium, and with sensitizers such as EMD-50733. 6 The extent to which such upward shifts occur at low calcium levels might again exacerbate diastolic effects. Lastly, a sensitizer may display Ca 2ϩ -dependent changes, so that effects at lower calcium concentrations are minimized, whereas shifts in the forceCa 2ϩ relation at systolic levels of calcium are manifest (type C).…”
Section: The Myofilament Force-ca 2؉ Relationshipmentioning
confidence: 99%
“…Clinical development was ultimately halted because of bioavailability limitations, but experimental studies provided many useful insights into the general drug class as noted in Figures 2 and 5. A recent further finding revealed greater potency of EMD-57033 in a mouse model in which a truncated TnI was overexpressed to mimic proteolytic changes reported in myocardial stunning, 6,64 which suggests that such drugs may be particularly suited to diseases with abnormal Ca 2ϩ sensitivity from altered regulatory thin-filament proteins, This would likely depend on the precise mechanism of action of the agent.…”
Section: Emd-57033mentioning
confidence: 99%